The Roles of IRF-8 in Regulating IL-9-Mediated Immunologic Mechanisms in the Development of DLBCL: A State-of-the-Art Literature Review - Cai, Mingyue; Chen, Na (Frontiers in Oncology, 2022)
Interferon regulatory factor 8 (IRF-8) is a transcription suppressor that functions through associations with other transcription factors, contributing to the growth and differentiation of bone marrow cells and the activation of macrophages. IRF-8 expression profoundly affects pathogenic processes ranging from infections to blood diseases. Interleukin-9 (IL-9) is a multipotent cytokine that acts on a variety of immune cells by binding to the IL-9 receptor (IL-9R) and is involved in a variety of diseases such as cancer, autoimmune diseases, and other pathogen-mediated immune regulatory diseases. Studies have shown that IL-9 levels are significantly increased in the serum of patients with diffuse large B-cell lymphoma (DLBCL), and IL-9 levels are correlated with the DLBCL prognostic index. The activator protein-1 (AP-1) complex is a dimeric transcription factor that plays a critical role in cellular proliferation, apoptosis, angiogenesis, oncogene-induced transformation, and invasion by controlling basic and induced transcription of several genes containing the AP-1 locus. The AP-1 complex is involved in many cancers, including hematological tumors. In this report, we systematically review the precise roles of IL-9, IRF-8, and AP-1 in tumor development, particularly with regard to DLBCL. Finally, the recent progress in IRF-8 and IL-9 research is presented; the possible relationship among IRF-8, IL-9, and AP-1 family members is analyzed; and future research prospects are discussed.